Energy and macronutrients intake of the swimming Spanish Olympic team in the CAR of Sierra Nevada - Mariscal-Arcas, M.; Carracedo, J.; Ribot, E.; Domingo, A.; Martin, T.; Fernández de Alba, M. C. (Archivos de medicina del deporte, 2008)
Nutritional assessment in elite athletes is essential to avoid nutritional deficiencies linked to athletic performance. This assessment is especially important during training at moderate altitude (2320m). The environmental changes can be exploited for the benefit of the sport performance. Nutritional assessment is especially important at moderate altitude. Sport performance has relationship with food quality of the swimmers. Objective: The aim of this study was to evaluate the diet of the Swimming Spanish Olympic Team during a stay in the CAR of Sierra Nevada before the Olympic Games in Beijing. Material and method: 9 swimmers (4 males and 5 females) were analysed (17-26 yrs) Dates were collected during may 2008 using a specific Diet Register created by the research team for sportspeople resident at the CAR of Sierra Nevada, in which the daily intake of all foods was recorded. The food composition tables of the national "Alimentación y Salud" programme were used for the nutritional evaluation of reported data. SPSS 15.0 software was used for the statistical study. Results: For swimmers males the mean energy intake was 2985.2Kcal/d (SD: 623.2), 329.4g/d (SD: 85.1) carbohydrates, 162.3g/d (SD:41.6) protein and 120.5g/d (SD: 39.6) lipids. For swimmers females the mean energy intake was 3153.1Kcal/d (SD: 775.0), 391.6g/d (SD:109.8) carbohydrates, 172.2g/d (SD:68.7) protein and 108.3g/d (SD: 35.1) lipids. Conclusion: The diet of the study population is generally moderate in terms of energy intake, according to data declared in the Register Dietetic-CAR Sierra Nevada possibly caused by the involuntary overestimation. It would important to studied each athlete (training, body composition, daily energy expenditure, c) to develop the nutritional requirements (energy, macro and micronutrients) for this population.